Clinical exome sequencing identifies novel CREBBP variants in 18 Chinese Rubinstein–Taybi Syndrome kids with high frequency of polydactyly. Issue 12 (22nd October 2019) - Yu, Sha; Wu, Bingbing; Qian, Yanyan; Zhang, Ping; Lu, Yulan; Dong, Xinran; Wang, Qing; Zhao, Xuemei; Liu, Renchao; Zhou, Wenhao; Wang, Huijun
Abstract: Background: Rubinstein–Taybi syndrome (RSTS) is a rare genetic disease characterized by broad thumbs and halluces, facial dysmorphisms, short stature, and intellectual disability. RSTS is mainly caused by de novo variants in epigenetics‐associated gene, CREBBP . To date, there is no cohort study of CREBBP variants in Chinese RSTS patients. Methods: In this study, 18 kids who meet the main criteria of RSTS were recruited. Molecular diagnoses were analyzed by clinical exome sequencing (CES), and the medical records were reviewed retrospectively. Results: Nineteen novel CREBBP variants in 18 RSTS patients were identified, including two missense, four nonsense, five frameshift, one splicing variants, and seven intragenic deletions. A higher incidence (37%, 7/19) of intragenic deletions was detected. One patient who had two de novo missense variants c.[4112T > A, 4118C > A] in cis and one patient who had a de novo frameshift variant c.5837delC in homozygous state (90%) were found in this study. Compared with the previously reported populations, seven clinical features were different, including the higher incidence of polydactyly, syndactyly, microcephaly, and micrognathia, and the lower incidence of angulated thumbs, autistic behavior, and epilepsy. One patient with obesity in the first year was diagnosed with CREBBP gene exon 2 deletion, was initially suspected of Prader–Willi syndrome. Conclusion: We reported the genetic and clinical information of 18 RSTS patients from Chinese population with novel CREBBP variants. This study provides a new insight into RSTS and illustrates the value of applying CES which increases the diagnostic yields and enhances the clinical care of RSTS patients. Abstract : We reported 18 RSTS cases with novel CREBBP variants, including two missense, four nonsense, six frameshift, one splicing variants, and seven deletions. Two special de novo variants were reported in this study: one patient was detected with two missense variants in cis and another patient confirmed with a frameshift variant (c.5837delC) in homozygous state (90%). Interesting, one patient had obesity was diagnosed with CREBBP gene exon 2 deletion, who was initially suspected of Prader‐Willi syndrome (PWS), while PWS DNA methylation testing revealed negative.